KERAGAMAN SIFAT KUALITATIF DAN KUANTITATIF SAPI KUANTAN PADA BERBAGAI TINGKATAN UMUR DIKECAMATAN BENAI - Restu Misrianti; Rona Perti Mustika; Arsyadi Ali (State Islamic University of Sultan Syarif Kasim Riau, 2018)
This research aims to know the diversity of the nature of qualitative and quantitative kuantan cows age on many levels in Benai District of Kuantan Singingi regency. The number of samples was observed 88 cows kuantan which consists of 71 cows female and 17 male cows with levels 0-6 months, 6-12 months, 12-18 months and 18-24 months. The parameters observed in the qualitative nature of hair and skin color is, horns shape and color away, while the nature of quantitative measurements of the body namely chest circumference, length, shoulder height, in the chest and hip height. The results showed that the qualitative nature of the cows kuantan females include the dominant hair color that is the color of tanned 35,21% white, curved Horn shape up and short horns and small alike 29.5% and the dominant leg color is 68% white and male cow whereas in kuantan, the dominant hair color that is the color of tanned 35,30% white, horned 53% not horned and short small 29% , and the dominant leg color is white 76%. Quantitative trait cow kuantan females include the dominant length is age 18-24 months 96,28 ± 10.70 cm, chest circumference: 20,71 ± 12.52 cm, in the chest: 43,28 ± 0.14 cm, shoulder height: 96,57 ± 7.25 cm and a height of hips: 101,71 ± 9.94 cm and while the average body size of cow kuantan males include the dominant length is aged 6-12 months 87 ± 6.05 cm, chest circumference of 6-12 months ± 16,52 112,75 cm chest, in 12-18 months 41,33 ± 1.53 cm shoulder height, age 18-24 months orders of 4.16 ± 91,67 cm high hip and age 12-18 months of 6.08 ± 101 cm.